The Influence of Problem-Based Learning on Elementary School Students' Interest in Science - Budhiman, Arief; Satifah, Oriza; Sari, Fita Permata (Impulse: Journal of Research and Innovation in Physics Education, 2022)
Elementary school students' problem-solving abilities must be developed so that they are accustomed to formulating solutions. This study aims to determine the effect of problem-based learning on students' interest in science at SD Muhammadiyah Majenang. The nonequivalent control group design was used in this quasi-experimental study. The participants in this study were fourth-grade students from SD Muhammadiyah Pahonjean and SD Muhammadiyah Cilopadang. Student questionnaires and documentation were used to collect data. The data analysis technique used a normality test, homogeneity test, and t-test. The Mann-Whitney test results show that the Asymp Sig. 0.000. This results that the problem-based learning model having an impact on SD Muhammadiyah Majenang students' interest in science. Teachers need to implement science learning using a problem-based learning model.